Providing continuity of care for people living with noncommunicable diseases in humanitarian settings: A qualitative study of health actors' experiences in Lebanon - C. Akik; Z. El Dirani; R. Willis; C. Truppa; C. Zmeter; S. Aebischer Perone; J. Roswall; R. Hamadeh; K. Blanchet; B. Roberts; M.F. Fouad; P. Perel; et al. (Journal of Migration and Health)
Objective: The burden of non-communicable diseases (NCDs) is increasing among populations living in humanitarian settings. Continuity of care (CoC) involves following an individual over time and across different levels of healthcare (management, longitudinal, informational and interpersonal continuity); it is an essential component of good quality, person-centred NCD care. Providing CoC is particularly challenging in humanitarian crises where health care access may be interrupted or restricted. This paper aimed to explore health actors’ experiences of continuity of hypertension and diabetes care for Syrian refugees and vulnerable Lebanese in Lebanon. Methods: We conducted 20 in-depth qualitative interviews with health actors, including eleven with health care providers at four urban-based health facilities supported by international humanitarian agencies that provide NCD care to Syrian refugees and vulnerable Lebanese, one representative of a governmental institution, one international delegate and seven humanitarian actors. Thematic analysis, combining inductive and deductive approaches, was guided by a conceptual framework for NCD models of care in humanitarian settings. We reported our findings against the conceptual framework's domains relating to health system inputs and intermediate goals, reflecting on their impact on the domains of CoC. Findings: Existing health system weaknesses and novel challenges (the economic crisis, COVID-19 pandemic and Beirut blast) to continuity of NCD care were identified. Health system input challenges: governance and financing (weakened governance, limited central financing, historical dependence on local NGOs for primary healthcare, a dominant private sector), health workforce (exodus of health care providers from the public system), inconsistent medicines and equipment supplies, and limited health information systems (no unified system across institutions or levels of care, lack of formal referral systems, and inconsistent facility-level data collection) contributed to limited public primary care, poorly integrated within a fragile, pluralistic health system. These factors negatively impacted the intermediate health system goals of access, standardisation and quality of NCD care for Syrian refugee and Lebanese patients, and collectively hampered the management, longitudinal, informational and interpersonal continuity of NCD care in Lebanon. Conclusion: We recommend that humanitarian actors continue the work underway with the Lebanese Ministry of Public Health to align with and strengthen health system inputs, including supporting health governance through the accreditation process, exploring new funding mechanisms, strengthening the workforce via task sharing and training, supporting the medication supply chain, improving access to facilities and service quality, and supporting the development, standardisation and interoperability of referral and information systems. In combination, these elements will support better CoC for people living with hypertension and diabetes in Lebanon.